Measurements of jet quenching using semi-inclusive hadron plus jet distributions in pp and central Pb-Pb collisions at √sNN=5.02 TeV - Acharya, S.; Adamova, D.; Rinella, G. Aglieri; Agnello, M.; Agrawal, N.; Ahammed, Z.; Ahmad, S.; Ahn, S. U.; Ahuja, I.; Akindinov, A.; Al-Turany, M.; Aleksandrov, D.; et al. (AMER PHYSICAL SOC, 2024)
The ALICE Collaboration reports measurements of the semi-inclusive distribution of charged-particle jets recoiling from a high transverse momentum (high p(T)) charged hadron, in pp and central Pb-Pb collisions at center-of-mass energy per nucleon-nucleon collision root s(NN) = 5.02 TeV. The large uncorrelated background in central Pb-Pb collisions is corrected using a data-driven statistical approach which enables precise measurement of recoil jet distributions over a broad range in p(T,ch jet) and jet resolution parameter R. Recoil jet yields are reported for R = 0.2, 0.4, and 0.5 in the range 7 < p(T,ch jet) < 140 GeV/c and pi/2 < Delta phi < pi, where Delta phi is the azimuthal angular separation between hadron trigger and recoil jet. The low-p(T,ch jet) reach of the measurement explores unique phase space for studying jet quenching, the interaction of jets with the quark-gluon plasma generated in high-energy nuclear collisions. Comparison of p(T,ch jet) distributions from pp and central Pb-Pb collisions probes medium-induced jet energy loss and intra-jet broadening, while comparison of their acoplanarity distributions explores in-medium jet scattering and medium response. The measurements are compared to theoretical calculations incorporating jet quenching.
Keywords: PROTON-PROTON COLLISIONS; NUCLEAR MODIFICATION; MOMENTUM DEPENDENCE; LEAD COLLISIONS; CROSS-SECTION; SUPPRESSION; ENERGY; MASS; Physics